Studies on multiple branching panicles in cardamom (Elettaria cardamomum Maton) - RAJENDRA HEGDE, S J ANKEGOWDA, V S KORIKANTHIMATH, M N VENUGOPAL, (Journal of Spices and Aromatic Crops, 1998)
Field investigations were carried out at Kodagu (Karnataka, India) to study the nature of branching of panicles in 49 entries of cardamom (EZettaria cardamomum) of Malabar type (CI-37, prostrate type). Considerable variations in the nature of branching and basal branching, terminal branching and uniform branching throughout the length of the main axis of the panicle were observed. The pattern of branching was secondary and tertiary in nature. The 49 entries were also assessed for growth and panicle characters and considerable variations were observed for number of tillers, number of bearing tillers, number of panicles per plant and number of branches per panicle. The number of panicles per plant ranged from 12-148 and number of branches ranged from 17-31 per panicle.